Synthesis and Biological Evaluation of Some New Benzimidazole Derivatives Bearing Dithiocarbamate Moiety as Potential Cholinesterase Inhibitors - Usama Abu Mohsen (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Purpose: The synthesis of eight new benzimidazole derivatives bearing dithiocarbamate moiety and subsequently their anticholinesterase activity evaluations were aimed in this present study. Material and Method: 2-Bromoacetylbenzimidazole react with dithiocarbamate salt derivatives and the resulted compounds were elucidated by 1H NMR, mass spectral data, and elemental analyses. Each derivative was evaluated for its ability to inhibit acetylcholinesterase (AChE) in vitro by using a modification of Ellman's spectrophotometric method. Results: The new compound 1-methyl-2{2'[(N,Ndimethylaminothiocarbamoylthio)-acetyl]}benzimidazole (2b) can be identified as promising anticholinesterase agent in vitro due to its moderate inhibition effect, which is about 37%, when compared with standard substance Donepezil under the same experimental conditions. Conclusion: In comparing with the reference standard, among the synthesized eight new compounds the only compound namely 1-methyl-2{2'[(N,Ndimethylaminothiocarbamoyl-thio)-acetyl]}benzimidazole (2b) has a promising anticholinesterase activity. [Cukurova Med J 2014; 39(4.000): 729-735]